Fashioned in the North : Nordic Histories, Agents and Images of Fashion Photography - Dahlgren, Anna (Nordic Academic Press, 2020)
This edited volume showcases new examples--previously untold stories of images, photographers, publications, and institutions --partly unknown outside the Nordic countries. The authors examine the reasons for and implications of this underexposure, taking on a photographic metaphor. While simultaneously challenging previously taken-for-granted ideas of the centre and periphery in this field, the book also widens the study of fashion photography. Notably, the hybridity of approaches may enrich future studies of fashion photography. In Fashioned in the North, fashion photography is viewed as a transnational phenomenon and a material object, as well as a medium that is part of a media system and a result of archival systems and history writings. Furthermore, the book displays how studies of fashion photography can be so much more than stories of a few names and iconic images or studies of individual and periodic style. Indeed, the study of fashion photography may be a prism through which we can uncover cultural, social, economic, and ideological aspects of society at present and in the past.